Anti-corruption education as an effort to form students with character humanist and law-compliant - Dewantara, Jagad Aditya; Hermawan, Yudi; Yunus, Dadang; Prasetiyo, Wibowo Heru; Efriani, Efriani; Arifiyanti, Fitria; Nurgiansah, T Heru (Jurnal Civics: Media Kajian Kewarganegaraan, 2021)
Anti-corruption education has a role in solving the problem of corruption. We can see from the increasing number of corruption cases that display on various social media. This phenomenon must prevent and eradicate the country's economy, country's economy, national values and state ideology. This article examines anti-corruption education as character building that emphasizes free will, individual behaviour through student potential. This study conducted using qualitative methods and literature study with the object of analysis from various references to books, articles and other media. The approach to this research uses normative-empirical methods as the basis for analyzing primary and secondary data. The results obtained were that anti-corruption education for students required the formation of a humanistic character, student knowledge about corruption, legal policies related to corruption cases and obedience and legal awareness of students in tertiary institutions to maintain a caring attitude towards the nation and state.